Relationship between soccer physical activity enjoyment and internet addiction among adolescents: the chain mediating effect of emotional self-efficacy and athlete participation - Shan, Liang; Che, Xiang; Wang, Haopeng; Li, Anzu; Ma, Ning; Shui, Yizhou (Frontiers in Psychology, 2025)
To explore the mechanism of adolescent school soccer players’ participation in Internet addiction behavior, this study surveyed 579 young soccer players from 18 primary and secondary schools in Shaanxi Province using the soccer athlete participation scale, physical activity enjoyment scale, emotional self-efficacy scale, and Internet addiction scale. The participants included 310 males, 260 females, 411 primary school students (8–12 years), and 159 junior high school students (12–15 years). The results show that: (1) Internet addiction is negatively correlated with the enjoyment of participating in soccer. (2) Through the mediation of soccer participation, soccer’s physical active enjoyment predicts Internet addiction. (3) Soccer physical actively enjoyment negatively predicts Internet addiction through the mediation of emotional self-efficacy. (4) Negative prediction of Internet addiction through the chain mediation of soccer athlete participation and emotional self-efficacy. This study constructed a chain mediating model with athlete participation and emotional self-efficacy as key mediating variables. This study provides a theoretical and practical basis for the intervention of Internet addiction through physical activity enjoyment and soccer athlete participation.